Enhancement of Mobile-Based Coffee Product Marketing and Stock Management Application Features: - - Khonaza, Mifta Janatun; Asriningtias, Yuli (Kirana Publisher (KNPub), 2024)
The advancement of information technology has driven innovation in facilitating various activities, including the small and medium-sized enterprise (SME) sector in coffee marketing. Challenges such as manual marketing, stock monitoring, and sales recap often result in inefficiencies and limited market reach. This study aims to develop a mobile and web-based application that optimizes stock management and transactions while adding a coffee delivery feature. This feature enables customers to order coffee online with direct delivery, while the redesigned user interface enhances a more intuitive user experience. With a more responsive and stable system, the application is expected to reduce manual errors, support more effective management, and expand digital market reach. This solution is designed to enhance customer convenience, business efficiency, and the competitiveness of coffee SMEs in the technology era.